Development and Implementation of AI Robot with Primary School Mandarin Level - Chen, Che Wen; Syu, Jyun-Ruei; Ou, Yang-Yen; Wang, Jhing-Fa (2022 10th International Conference on Orange Technology (ICOT), 2022)
With the increasing popularity of artificial intelligence, the technologies used by robots are changing rapidly. We propose a robotic system that can handle Mandarin-related problems, effectively dealing with Mandarin phonetic transcription, multiple-option reading comprehension, text error correction, similarity judgment, and keyword search. The experimental results show that using the national language assessment of grades 1-6 in primary schools, the highest score on the national language assessment is 90, and the lowest is 63, which is consistent with the actual score-provided by Shekou National Primary School for Mandarin assessment. Furthermore, more than half of the average scores in each subject are higher than the low standard (average of the bottom 25 % ) and even higher than the high standard (average of the top 25%). Through this system, the machine can reach the national language level of primary school students.